Taming the great desert : Adam in the prehistory of Oman - Gernez, Guillaume, (Archaeological heritage of Oman ;, 2019)
Located at the margins of the Rub Al-Khali desert, a place of interactions between settled & nomadic populations, the Adam oasis occupies a pivotal role in the history of Oman. However, almost nothing was known about its foundation & early developments. In 2006, the French Archaeological Mission in Central Oman began the exploration of the area. After 10 years of field research using innovative methods & technologies, much is revealed about the importance of Adam in the prehistory & early history of Oman. This is a monograph about the research carried out at Adam & it includes chapters written by specialists directly involved in the field activities. Each major period is described, including evidence of Palaeolithic occupation, Neolithic settlements, Early & Middle Bronze Age necropolises, Iron Age ritual sites & also an ethnographic study of the traditional water sharing within the oasis.